Plants of ethnomedicinal importance from Yawalforest area Yawal, Jalgaon (India) - S.S. Yadav2, Vidya Patil A.1 and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ethnobotany is holistic study, which involves the reciprocal and dynamic aspect of interactions of Adivasis people with plants. There are thousands of plants that yields medicines are very useful to mankind .The plants which naturally contain certain chemical constituents having therapeutic properties are called medicinal plants .Several plants in Yawal forest area have potential of better economic exploitation.Tribal having tremendous ethnomedical knowledge that has passed from one generation to the next generation.Yawal forest area is store house of numerous medicinal plants, various plants are used traditionally by Pawara people in skin , diseases , cough , cold , asthma, jaundice, fever , indigestion etc. Present article deals with some important plants used to cure cough , cold , asthma, by Pawara people in Yawal forest area .12 species belonging to 11 families and their traditional uses for curing respiratory diseases are recorded.